2002
DOI: 10.1046/j.1440-1681.2002.03682.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Kad‐1229, A Novel Hypoglycaemic Agent, On Plasma Glucose Levels After Meal Load In Type 2 Diabetic Rats

Abstract: 1. The effects of KAD-1229 (a novel non-sulphonylurea agent), voglibose (an alpha-glucosidase inhibitor) and nateglinide (a non-sulphonylurea antihyperglycaemic agent) on hyperglycaemia induced by a meal load were assessed in diabetic rats. 2. KAD-1229 suppressed the increase in plasma glucose levels seen after a meal load and the area under the curve for plasma glucose levels (AUCglucose) up to 5 h after the meal load. 3. Voglibose also suppressed the increase in plasma glucose levels; however, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…5A). Rapid-and short-acting insulin secretagogues or ␣-glucosidases have often been evaluated in mildly diabetic rats (i.e., rats with a degree of diabetes severity similar to that induced here (Ikenoue et al, 1997;Ichikawa et al, 2002). Sergliflozin provides a parallel to these antidiabetics as a way of improving postprandial hyperglycemia, at least in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Rapid-and short-acting insulin secretagogues or ␣-glucosidases have often been evaluated in mildly diabetic rats (i.e., rats with a degree of diabetes severity similar to that induced here (Ikenoue et al, 1997;Ichikawa et al, 2002). Sergliflozin provides a parallel to these antidiabetics as a way of improving postprandial hyperglycemia, at least in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…plasma half‐life of the drug) are as important in determining the risk of hypoglycaemia. In vivo studies using nondiabetic Wistar and diabetic GK rats suggested that S 21403 (KAD‐1229) could be a suitable agent for controlling postprandial hyperglycaemia, since it was able to suppress the increase in plasma glucose seen after a meal load up to 5 h after the meal ( Ichikawa et al ., 2002 ). The drug was also effective when administered orally to diabetic dogs ( Misawa et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the present study showed that both acute and 8 weeks of S3226 treatment lowered the postprandial plasma glucose levels remarkably. This beneficial effect on postprandial glucose surges was also observed in other antidiabetic drugs, such as insulin secretagogues or glucosidases . Given that SGLT1 inhibition is known to be associated with prominent side effects, such as diarrhoea, dehydration and malabsorption, we also considered if similar side effects could arise after prolonged application of NHE3 inhibitors.…”
Section: Discussionmentioning
confidence: 79%